Oestrogen-soaked vaginal packing for decubitus ulcer in advanced pelvic organ prolapse: a case series. Issue 7 (July 2016) - Abdullah, Bahiyah; Khong, Su; Tan, Peng
Abstract Introduction Cervicovaginal decubitus ulceration is a well-known complication of advanced pelvic organ prolapse (POP). There is no consensus for its management. This case series describes the outcome of using repeated vaginal packs soaked with oestrogen cream to reduce POP and promote decubitus ulcer healing. We aimed to investigate the speed of ulcer healing and endometrial safety with this regimen. Methods This was a retrospective study of patients with stage 3 or 4 POP and intact uterus with decubitus ulcer who were planned for surgery that included hysterectomy after ulcer healing. Vaginal packs are replaced at least biweekly—or more frequently if extruded—until ulcer resolution. Results Thirteen patients were studied. Mean age was 69 ± 6 years and mean duration of menopause was 19 ± 6 years. Nine patients had a single ulcer and four had multiple ulcers. Mean ulcer diameter was 2.8 ± 1.5 cm and mean duration for ulcer healing was 26 ± 14 days. Hysterectomy and pelvic floor reconstruction was performed a median of 5 (range 0–153) days after ulcer healing was first noted. Histopathological examination of the endometrium following hysterectomy showed three specimens with endocervical hyperplasia; one had concurrent proliferative endometrium, two had simple endometrial hyperplasia and another two had proliferative endometrium. Conclusion Oestrogen-soaked vaginal packing is a viable option for managing a decubitus ulcer in advanced POP. We document a measurable impact on the endometrium with this short-term preoperative regimen. Further research is needed to evaluate its efficacy in promoting ulcer healing and endometrial safety.